Oral creatine supplementation and athletic performance: a critical review - Juhn, M. S.; Tarnopolsky, M. (Clinical Journal of Sport Medicine, 1998)
OBJECTIVE: To review and summarize the current data on oral creatine supplementation regarding its potential efficacy in athletic performance, mechanism of action, and metabolism. DATA SOURCES AND STUDY SELECTION: Medline was searched using terms relating creatine supplementation to athletic performance. Studies that evaluated the effects of oral creatine supplementation on exercise performance in humans were selected for inclusion. Selected studies on muscle metabolism and exercise physiology were included if they provided useful information relative to creatine. Additional references were reviewed from the bibliographies of selected studies. DATA EXTRACTION AND SYNTHESIS: To summarize efficacy, extracted data were listed in table format, grouping studies together by type of activity and efficacy on performance. Whenever possible, the effect of creatine supplementation was quantified. Proposed explanations for creatine's efficacy or lack thereof in a particular type of activity were formulated. CONCLUSIONS: In laboratory settings, creatine supplementation is ergogenic in repeated 6-30-second bouts of maxima stationary cycling sprints. The data on a single sprint or first-bout sprint of any kind are inconsistent. The data regarding creatine's ergogenic effects on ass-dependent activities, such as running and swimming, are not convincing, perhaps because of the side effect of weight gain from water retention. Studies on weight lifting suggest that creatine improves strength possibly by increasing myofibrillar protein synthesis however, more study is needed to prove this. No ergogenic effects on submaximal or endurance exercise are evident Individual response to creatine supplementation can vary greatly.